Regulations, standards and certification for agricultural export: A practical manual for producers and exporters from West Africa - Coulibaly, Aïcha L.; Liu, Pascal (CTA / FAO, 2006)
Exporting certified agricultural products can be a complex process. Written to help agricultural producers understand the certification procedures, the booklet covers voluntary certification schemes and their importance, advantages and constraints. It also describes the main import regulations in the European Union, Japan and the USA.